Cobalt PNCNHC 'pincers': ligand dearomatisation, formation of dinuclear and N2 complexes and promotion of C–H activation. Issue 13 (13th January 2016) - Simler, Thomas; Braunstein, Pierre; Danopoulos, Andreas A.
Abstract : Ligand dearomatisation in Co II phosphino-picoline NHC-type pincers and dicobalt complexes result from side-arm metalation or C–H activation at the NHC backbone; in the latter case, an 'anionic dicarbene' originates from a dearomatised Co I –N2 complex. Abstract : Studies of ligand dearomatisation in cobalt phosphino-picoline N-heterocyclic carbene (PNC NHC )-type pincers have revealed the formation of dinuclear cobalt complexes by either side-arm metalation or C–H activation at the NHC backbone; in the latter case, the product complex, featuring an 'anionic dicarbene', originated from a dearomatised Co I –N2 complex.